The pathogenesis of murine coronavirus infection of the central nervous system - Hosking, Martin P. (2010)
Mouse hepatitis virus (MHV) is a positive strand RNA virus that causes an acute encephalomyelitis which later resolves into a chronic fulminating demyelinating disease. Cytokine production, chemokine secretion, and immune cell infiltration into the central nervous system are critical to control viral replication during acute infection. Despite potent anti – viral T lymphocyte activity, sterile immunity is not achieved, and MHV chronically persists within oligodendrocytes. Continued infiltration and activation of the immune system, a result of the lingering viral antigen and RNA within oligodendrocytes, lead directly to the development of an immune – mediated demyelination that bears remarkable similarities, both clinically and histologically, to the human demyelinating disease multiple sclerosis. MHV offers a unique model system for studying host defense during acute viral infection and immune – mediated demyelination during chronic infection.